Fecal microbiota transplantation mitigates respiratory infection in rats exposed to hypobaric hypoxia by modulating the NLRP3 inflammasome and mucosal immunity - Huan Wang; Zhenyan Wu; Yaolei Zhang; Lijun Tang; Guangqing Shi; Lijie Ma; Zhu Huang; Jing Zhou (PLoS ONE, 2026)
Objective To investigate the role of the gut-lung axis in respiratory infection under hypobaric hypoxia and the therapeutic potential of fecal microbiota transplantation (FMT). Methods Rats were exposed to hypobaric hypoxia (simulated 5000 m) for 14 days. Gut microbiota and serum short-chain fatty acids (SCFAs) were analyzed via 16S rRNA sequencing and GC-MS. Rats were then infected with Streptococcus pneumoniae and treated with FMT. Lung inflammation, NLRP3 inflammasome activity, cytokines, bacterial load, and secretory IgA (sIgA) were assessed. Results Hypobaric hypoxia triggered gut dysbiosis, marked by reduced abundance of Firmicutes D and Lactobacillus, elevated Bacteroidota , and decreased SCFA levels..FMT restored microbiota composition, increased acetic and butyric acid levels, and attenuated lung inflammation. FMT also enhanced NLRP3 inflammasome activation (NLRP3, ASC, Caspase-1), elevated IL-1β, IL-6, and TNF-α in BALF, reduced bacterial colonies, and increased airway sIgA in infected rats. Conclusions FMT alleviates hypobaric hypoxia-aggravated respiratory infection by restoring gut microbiota, modulating SCFAs, and enhancing NLRP3-mediated mucosal immunity, highlighting the gut-lung axis as a therapeutic target.